2012
DOI: 10.1007/s00784-012-0715-3
|View full text |Cite
|
Sign up to set email alerts
|

Digital method for quantification of circumferential periodontal bone level using cone beam CT

Abstract: This new approach of radiographically assessing circumferential periodontal bone level using CBCT data shows a first promising attempt of accurate detection of periodontal bony defects. Yet, possible negative impact of further clinical parameters in terms of artifact occurrence will have to be furthermore carefully investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 23 publications
1
60
0
5
Order By: Relevance
“…In the search of literature, we found that most of the studies focusing on the measurement accuracy of periodontal bone loss/defect were in vitro studies. [7][8][9][15][16][17][18][19][20] Only one in vivo study was performed on the measurement accuracy of bone defects on the maxillary molar. 21 Although there are a few more in vivo studies with regard to periodontal bone height measurement using CBCT, two of which are case reports, 22,23 others compared different methods of measuring guided tissue regeneration-treated bone defects and furcation lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In the search of literature, we found that most of the studies focusing on the measurement accuracy of periodontal bone loss/defect were in vitro studies. [7][8][9][15][16][17][18][19][20] Only one in vivo study was performed on the measurement accuracy of bone defects on the maxillary molar. 21 Although there are a few more in vivo studies with regard to periodontal bone height measurement using CBCT, two of which are case reports, 22,23 others compared different methods of measuring guided tissue regeneration-treated bone defects and furcation lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Various imaging and estimation techniques have been used in many studies to assess alveolar bone [13,14]. It is clear that 3D CBCT imaging has the greatest advantage over 2D intraoral radiography for evaluating buccal and lingual alveolar bone [15].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have analyzed CBCT applications in implantology [5, 6], oral surgery [68], endodontics [9] and orthodontics [10]. Studies conducted with database images [11], human cadavers [1219], swine mandibles [12, 20, 21] and patients with chronic periodontitis [2224] have analyzed CBCT performance in diagnosis and treatment planning in periodontics. These studies suggest that CBCT is more accurate than periapical radiographs in detecting bone craters, dehiscence, fenestration and furcation involvement.…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest that CBCT is more accurate than periapical radiographs in detecting bone craters, dehiscence, fenestration and furcation involvement. Nevertheless, as regards one- or two-wall infrabony defects and horizontal bone loss, CBCT superiority over periapical radiographs remains controversial [1216, 19, 21, 23], because some studies did not compare CBCT performance to periapical radiographs [19, 23]. Even when considering the studies in which comparisons were made, there was no unanimity in favor to CBCT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation